2021
DOI: 10.3390/ijms22115606
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Leukotriene Receptor Antagonist Montelukast in Treatment of Neuroinflammation in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder where misfolded alpha-synuclein-enriched aggregates called Lewy bodies are central in pathogenesis. No neuroprotective or disease-modifying treatments are currently available. Parkinson’s disease is considered a multifactorial disease and evidence from multiple patient studies and animal models has shown a significant immune component during the course of the disease, highlighting immunomodulation as a potential treatment strategy. The immune changes occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 99 publications
(118 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, several other agents have been proven to exert a neuroprotective action on PD, including celecoxib (a selective COX-2 inhibitor) [ 185 ], montelukast (a leukotriene receptor antagonist) [ 186 , 187 , 188 , 193 ], and tocopherol (vitamin E) [ 194 , 195 ]. Therapy with the aid of celecoxib (< 20 μM) has been shown to reinstate SH-SY5Y cells that had been potentially subjected to paraquat and 6-OHDA prompted damage [ 185 ].…”
Section: Experimental Studies Portraying the Deep Insights Into The Neuroprotective Role Of Ppar Agonists In Pdmentioning
confidence: 99%
“…Furthermore, several other agents have been proven to exert a neuroprotective action on PD, including celecoxib (a selective COX-2 inhibitor) [ 185 ], montelukast (a leukotriene receptor antagonist) [ 186 , 187 , 188 , 193 ], and tocopherol (vitamin E) [ 194 , 195 ]. Therapy with the aid of celecoxib (< 20 μM) has been shown to reinstate SH-SY5Y cells that had been potentially subjected to paraquat and 6-OHDA prompted damage [ 185 ].…”
Section: Experimental Studies Portraying the Deep Insights Into The Neuroprotective Role Of Ppar Agonists In Pdmentioning
confidence: 99%
“…The pattern of serum TNF-α concentration increment through the 5 th , 10 th , and 15 th day after diagnosis, (A) for COVID without chronic disease group, (B) for COVID with chronic disease group TNF-α concentration was evaluated for all age subgroups on the 5th, 10th, and 15th days after diagnosis; the results showed no significant difference among the different age subgroups on the 5th and 10th days for COVID without chronic disease. While on the 15th day, a significant (P<0.01-P<0.001) difference was found between the (60-69) age subgroup and the (40-49), (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), (20-29) age subgroup as shown in (Figure -8-). For COVID with chronic disease in the (60-69) age subgroups, the TNF-α concentration was significantly (P<0.05-P<0.0001) higher than in other age subgroups.…”
Section: Figurementioning
confidence: 79%
“…Employment of agents pertaining to the class of monoamine oxidase B (MAO-B) and catechol-O-methyltransferase (COMT) blockers can successfully regulate DA deprivation in the brain [ 82 ]. Aside from that, non-steroidal anti-inflammatory drugs (NSAIDs) (aspirin and ibuprofen) [ 83 ], leukotriene receptor antagonist (montelukast) [ 84 ], vitamins (B 3 , D, E, and C) [ 85 ], alcohol imbibing [ 86 ], smoking [ 86 ], caffeine intake [ 87 ], and physical exercise [ 88 ] have been demonstrated to render significant neuronal protection in PD. Recent investigation has revealed that escalated alcohol consumption possesses safeguarding effect over the risk of PD (with odds ratio 0.79; 95% confidence interval 0.65–0.96; probability value = 0.021), with the significant involvement of alcohol dehydrogenase 1B [ 86 ].…”
Section: Parkinson’s Disease: Etiological Factors Pathogenic Events and Treatmentmentioning
confidence: 99%